Community leadership development: a case story of neighborhood revitalization in the El Dorado neighborhood - Duarte, Michael (Center for Leadership Equity and Research)
The purpose of this paper is to examine an initiatives approach to community revitalization in the El Dorado neighborhood using a place based approach to the development of leaders in the community.